USE OF T-SHAPED TOOTH IN A DIRECT CURRENT MACHINE WITH A WINDLESS ROTOR - KOSENKOV, Volodymyr; IVLIEV, Dmytro; VYNAKOV, Oleksandr; SAVOLOVA, Elvira; YARMOLOVYCH, Viktoria (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The electric direct current machine with a windingless rotor (DCWR) is significantly different from the classic direct current machine; its magnetic system does not have a common yoke and consists of a number of magnetically loose teeth and grooves open on both sides. The presence of grooves in which there is no bottom creates a number of air gaps, which leads to a decrease in the magnetic conductivity of the magnetic conductor in the transverse direction, which, again, leads to a weakening of the reaction field of the Фa armature and the rejection of additional poles and compensation winding. Therefore, the size of the working air gap can be reduced to the minimum possible value from a technological point of view. According to the structural schemes, the DCWR belongs to the type of induction machines with two stationary windings on the stator and a toothed magnetic conductor of the rotor, in which the magnetic induction in the working air gap changes only in magnitude without changing the sign. Therefore, the rotor in the DCWR is not remagnetized and is made of ordinary structural steel. The inductor type of the magnetic system allows having only one, common for all poles, excitation winding in the DCWR, and the rotor is very similar to the rotor of multi-pole synchronous machines with permanent incorporated magnets. At the same time, DCWR does not have permanent magnets, which allows to significantly reduce the cost of an electric machine. Replacing straight teeth with T-shaped ones allows you to significantly increase the efficiency of the DCWR design by improving its heat dissipation. The results of calculations and modeling of the stationary thermal field presented in the article show that the use of T-shaped teeth allows you to significantly increase the overload capacity of the DCWR or increase its power.